ANALISIS KAUSALITAS ZAKAT DAN KEMISKINAN DI KOTA PEKANBARU PERIODE 2011(Q1) – 2019(Q4) - Nurhayana, Delwani; Rosyetti, Rosyetti; Rahmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of the research was to determine the causality of zakat and poverty in Pekanbaru City Period 2011 (Q1) - 2019 (Q4). Data used in this research is time series data from 2011 (Q1) to 2019 (Q4), sourced from Badan Amil Zakat Nasional (BAZNAS), Central Bureau of Statistics (BPS). Data used in this research are secondary data that are time series. The analysis method used is Vector Autoregression (VAR). The analysis shows that in the long run zakat and poverty have no long-term relationship.using software E-Views version 10. The result of the research shawed in the long run that in the long run, zakat and poverty have no influence. The causality test shawed that there is no causality relationship between zakat and poverty in Pekanbaru City 2011 (Q1) - 2019 (Q4).Keywords: Zakat, Proverty, and Vector Autoregression (VAR).